Does the addition of oxaliplatin to preoperative chemoradiation benefit cT4 or fixed cT3 rectal cancer treatment? A subgroup analysis from a prospective study. Issue 12 (December 2016) - Wiśniowska, K.; Nasierowska-Guttmejer, A.; Polkowski, W.; Michalski, W.; Wyrwicz, L.; Pietrzak, L.; Rutkowski, A.; Malinowska, M.; Kryński, J.; Kosakowska, E.; Zwoliński, J.; Winiarek, M.; et al.
Abstract: Background: Whether there is any benefit derived from adding oxaliplatin to fluoropyrimidine-based preoperative chemoradiation is currently unknown in cases of advanced cT3 or cT4 tumours. Our aim was to evaluate this issue by analysing a randomized trial, which compared two schedules of preoperative treatment (chemoradiation vs. 5 × 5 Gy with 3 cycles of consolidation chemotherapy) for cT4 or fixed cT3 rectal cancer. Patients and methods: Delivery of oxaliplatin was mandatory to the first part of the study. For the second part, its delivery in both treatment-assigned groups was left to the discretion of the local investigator. We analysed a subgroup of 272 patients (136 in the oxaliplatin group and 136 in the fluorouracil-only group) from institutions that had omitted oxaliplatin in the second part of the study. Results: Circumferential resection margin negative (CRM−) status rate was 68% in the oxaliplatin group and 70% in the fluorouracil-only group, p = 0.72. The pathological complete response rate (pCR) was correspondingly 14% vs. 7%, p = 0.10. Following multivariable analysis, when comparing the CRM− status in the oxaliplatin group to the fluorouracil-only group, the odds ratio was 0.79 (95 CI 0.35–1.74), p = 0.54; there being no interaction between concomitant chemoradiation and 5 × 5 Gy with consolidation chemotherapy; pinteraction  = 0.073. For pCR, the corresponding results were 0.47 (95 CI 0.19–1.16), p = 0.10, pinteraction  = 0.84. Conclusion: No benefit was found of adding oxaliplatin in terms of CRM nor pCR rates for either concomitant or sequential settings in preoperative radiochemotherapy for very advanced rectal cancer.